2003
DOI: 10.1007/s00104-003-0679-6
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-Tumor der Lunge

Abstract: Clear cell tumors of the lung are commonly primary, clear-cell, bronchial carcinomas or metastasis of a renal cell carcinoma. Compared to this, pulmonary sugar tumor is a rare entity. A large intracellular content of glycogen and immunohistochemical procedures lead to diagnosis. The demonstration of the premelanosomal protein HMB-45 is considered as proof, but this is not airtight. We present a case of metachronic, benign, and HMB-45-negative sugar tumor of the lung after hypernephroma and give a review of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…2,13 Also, Kulchisky cells were proposed to be a possible origin of clear cell tumor of the lung, because of the dense-core type granules seen in some of the tumor cells. 14 Recently, Gaffey et al 8 reported that clear cell tumor of the lung demonstrated melanocytic differentiation, as evidenced by HMB-45/50-positive cells and tumor melanosomes. However, the histogenesis of the tumor remains unknown.…”
Section: Discussionmentioning
confidence: 98%
“…2,13 Also, Kulchisky cells were proposed to be a possible origin of clear cell tumor of the lung, because of the dense-core type granules seen in some of the tumor cells. 14 Recently, Gaffey et al 8 reported that clear cell tumor of the lung demonstrated melanocytic differentiation, as evidenced by HMB-45/50-positive cells and tumor melanosomes. However, the histogenesis of the tumor remains unknown.…”
Section: Discussionmentioning
confidence: 98%